The “Heretics” Hermeneutics: Bosnia and Balkan Bogomils in the Mirror of Modern Hungarian Literature As Potential(Borrowed?) Theaters of Multidimensional Orientalism - Marton Ivanyi (Journal of Balkan Studies)
In Hungary, situated in Central-Eastern Europe, the historical and cultural investigation of its relationship with the Balkans holds particular relevance due to the country’s unique and shifting historical position. Hungary has experienced distinct phases in its history: as a medieval middle power, later as a territory under Austrian rule, and subsequently as a state-forming entity within the Austro-Hungarian Monarchy. This progression has shaped Hungary’s perception of its neighbors and its role within European ideological currents, particularly those influenced by Orientalist discourses. The portrayal of the Bosnian (primarily identified – and subject to historical debate – as "Bogomils")in Hungarian historical literature is a compelling case in point. While not explicitly tied to imperial expansionist ambitions, such representations reflect European tendencies of “Othering,” where the “heretics” – often dismissed as heretics, tribal, or primitive – were situated in opposition to Western or Catholic norms. This dynamic was further complicated by Hungary’s intermediary status between Western Europe and the Balkans, creating a cultural and epistemological space that was neither fully “Orientalized” nor wholly part of the Western Occident. Hungary’s historical entanglement with the Balkans, therefore, offers a nuanced vantage point from which to examine Orientalist tendencies. These explorations are further elevated by the ideological debates surrounding the continuity between the medieval Bogomils and the later Bosnian Muslim population. The widely challenged notion that the Bogomils would have been "predecessors" of Bosnian Muslims adds another layer of ideological tension, particularly within critiques of Islam, which often bear a degree of ideological saturation. At first glance, Hungary’s portrayals of the Bosnian Christians cannot be isolated from broader European perceptions of Islam, where the historical Crusades, medieval animosities, and Enlightenment-era Orientalist narratives intersect. However, the Hungarian corpus itself rarely engages with the Bogomils as proto-Muslims, a narrative more prevalent in earlier Western and later Balkan discourses. Instead, Hungarian representations tend to emphasize the "sect"’s heretical nature, aligning more closely with medieval historiographical traditions than with ideological critiques of Islam. In this context, Hungary’s role as both a subject and an actor in these historical frameworks underscores the relevance of analyzing its cultural and literary portrayals of the Balkans and the Bosnia’s legacy. This dual position allows for critical insight into the hierarchical nature of Orientalism while also accounting for Hungary’s unique historical trajectory and its layered relationship with both “East” and “West.”